Group O RBCs: where is universal donor blood being used. Issue 4 (20th March 2017) - Barty, R. L.; Pai, M.; Liu, Y.; Arnold, D. M.; Cook, R. J.; Zeller, M. P.; Heddle, N. M.
Abstract : Background: There have been recurrent shortages of group O blood due to insufficient inventory and use of group O blood in ABO non‐identical recipients. We performed a 12‐year retrospective study to determine utilization of group O Rh‐positive and Rh‐negative red blood cells (RBCs) by recipient ABO group. Reasons for transfusing group O blood to ABO non‐identical recipients were also assessed. Methods: Utilization data from all group O Rh‐positive and Rh‐negative RBCs transfused at three academic hospitals between April 2002 and March 2014 were included. Data were extracted from Transfusion Registry for Utilization Surveillance and Tracking, a comprehensive database with inventory information on all blood products received at the hospitals. Extracted data included product type, ABO and Rh, final disposition (transfused, wasted, outdated), and demographic and clinical data on all patients admitted to hospital. Descriptive statistics were performed usingsas 9.3. Results: There were 314 968 RBC transfusions: 151 645 (48·1%) were group O, of which 138 136 (91·1%) RBC units were transfused to group O individuals. ABO non‐identical recipients received 13 509 group O RBCs (8·9%). The percentage of group O RBCs transfused to ABO non‐identical recipients by fiscal year varied from 7·8% to 11·1% with a steady increase from 2011 to 2013. Reasons for this included: trauma, outdating, outpatient usage and shortages. Conclusion: The practice of transfusing O RBCs to non‐O individuals has been increasing. Specific hospital and blood supplier policies could be targeted to change practice, leading to a more sustainable group O red blood cell supply.